Paediatric humeral supracondylar fractures. Issue 9 (September 2020) - Talbot, Christopher; Madan, Sanjeev
Abstract: The supracondylar humeral fracture is the most common elbow fracture in children, accounting for just under one-fifth of all paediatric fractures and 60% of paediatric elbow fractures. Modifications of the Gartland classification have been made over the years. The mainstay treatment option is that of closed reduction and percutaneous wiring. However, there remains no gold standard in the management of this injury. Outcomes from other treatment options, including traction and external fixator application have been described and report good results. There remains controversy in the wiring configuration used, and there is no consensus on the approach to be used when faced with an irreducible fracture. This article aims to provide an up-to-date overview of the current practices in the management of this common injury, including the 'pink pulseless' hand, 'poorly perfused white' hand, surgical techniques, and the associated complications that can ensue.